Pemaknaan Hadis-Hadis Hijrah dalam Pandangan Masyarakat Pasuruan Jawa Timur - Fajar Shodik, Ahmad; Zulfan Nabrisah; Ummul Khoiriyah (Advances in Humanities and Contemporary Studies, 2022)
Hijrah is a journey to something better than before. Thus, intention is the main motivation in making hijrah in order to gain the pleasure of Allah SWT. Recently, there has been an invitation to emigrate, in the sense of making changes to be better than before, both physical and psychological changes. The call for hijrah itself occurs in almost all Muslims in Indonesia, especially among women, the word hijrah seems to be a trending conversation. Hadith, which is the second source of Islamic law after the Qur’an, plays an important role as a source of reference. Therefore, it is important to understand the meaning of the hijrah hadiths in the paradigm of society in the Pasuruan area, East Java. So that it can be seen how the meaning of the hijrah hadiths in the understanding of the people in the Pasuruan area, East Java. And to find out how the form of practice or accent of hijrah is carried out by the people of Pasuruan, East Java. So, later in this article, it is known that the understanding of the Pasuruan community, namely community leaders, mothers, female students and teenagers, that they interpret hijrah as changing themselves to be better individuals than before, and leaving bad deeds that have been done in the past. So from that understanding they migrated in the form of improving worship such as praying five times a day, closing the genitals, carrying out sunnah prayers such as sunnah prayers and sunnah fasting and other sunnah practices in an effort and as a form of change for the better.